Prediction of human rotavirus serotype by nucleotide sequence analysis of the VP7 protein gene. - Green, K Y (1988)
Human rotavirus field isolates were characterized by direct sequence analysis of the gene encoding the serotype-specific major neutralization protein (VP7). Single-stranded RNA transcripts were prepared from virus particles obtained directly from stool specimens or after two or three passages in MA-104 cells. Two regions of the gene (nucleotides 307 through 351 and 670 through 711) which had previously been shown to contain regions of sequence divergence among rotavirus serotypes were sequenced by the dideoxynucleotide method with two different synthetic oligonucleotide primers. The resulting nucleotide sequences were compared with the corresponding sequences from rotaviruses of known serotype (serotype 1, 2, 3, or 4). A total of 25 field isolates and 10 laboratory strains examined by this method exhibited marked sequence identity in both areas of the gene with the corresponding regions of 1 of the 4 reference strains. In addition, the predicted serotype from the sequence analysis correlated in each case with the serotype determined when the rotaviruses were examined by plaque reduction neutralization or reactivity with serotype-specific monoclonal antibodies. These data suggest that as a result of the high degree of sequence conservation observed among rotaviruses of the same serotype, it is possible to predict the serotype of a rotavirus isolate by direct sequence analysis of its VP7 gene.